A seasonal OH minimum region over the Indian Ocean?. (15th February 2023) - Kuttippurath, J.; Ardra, D.; Raj, S.; Feng, W.
Abstract: As the hydroxyl radical (OH) is the cleansing agent of the atmosphere, reduction in its concentration is a great concern for air quality and transport of trace gases across the latitudes and altitudes. In addition, OH determines the lifetime of most trace gases and non-CO2 greenhouse gases in the atmosphere. Since many pollutants have adverse health effects and are greenhouse gases, the changes in OH concentrations directly or indirectly affect public health and climate. Our analysis with OH data (from Tropospheric Emission Spectrometer and Copernicus Atmosphere Monitoring Service reanalyses) for the past 14 (2005–2018) years finds an OH minimum region over Indian Ocean, in the eastern Bay of Bengal at 6°–14° N and 92°–95° E. The Indian Ocean OH minimum reaches to 15 × 10 4 molec.cm −3 in April, and a secondary minimum of 18 × 10 4 molec.cm −3 in September–November. This seasonal minimum found around the Andaman and Nicobar Islands also hosts an active volcano, which releases noticeable amount of SO2 (OH sink) throughout the year. In addition, the biomass burning in spring and thus, the distribution of CO has a profound influence on the OH distribution in this region as Southeast Asia is one of the global hotspots of biomass burning, and the Indian Ocean OH minimum is located near that region. The El Niño and La Niño events also control the tropospheric ozone and CO distribution, and thus the interannual variability of OH minimum there. The WACCM model simulations reproduce the general latitudinal distribution and average seasonal cycle of OH, but not the extreme minimum OH values, although the simulations show the annual minimum in winter (December–January) in both ocean regions, which demands dedicated studies using chemical transport models. Therefore, this study reveals a seasonal OH minimum over Indian Ocean, which is very likely to influence the regional air quality and trace gas transport in the tropics. Graphical abstract: Image 1 Highlights: There exists a seasonal OH minimum region over Indian Ocean in spring. A secondary minimum in autumn, but values are slightly higher than that in spring. SO2, CO, O3 and H2 O chemistry play a key role in the observed minimum in the region. The OH minimum can affect the air quality in the Indian Ocean region.